Sodium Lignosulfonate as an Extracting Agent of Methylene Blue Dye Using a Polymer-Enhanced Ultrafiltration Technique - Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2024)
The purpose of this research was to evaluate the efficacy of sodium lignosulfonate (LS) as a dye adsorbent in the removal of methylene blue (MB) from water by polymer-enhanced ultrafiltration. Various parameters were evaluated, such as membrane molecular weight cut-off, pH, LS dose, MB concentration, applied pressure, and the effect of interfering ions. The results showed that the use of LS generated a significant increase in MB removal, reaching an elimination of up to 98.0 % with 50.0 mg LS and 100 mg L−1 MB. The maximum MB removal capacity was 21 g g−1 using the enrichment method. In addition, LS was reusable for up to four consecutive cycles of dye removal-elution. The removal test in a simulated liquid industrial waste from the textile industry was also effective, with a MB removal of 97.2 %. These findings indicate that LS is highly effective in removing high concentrations of MB dye, suggesting new prospects for its application in water treatment processes. © 2024 Elsevier B.V.